2021
DOI: 10.3390/genes12020235
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in NUT Carcinoma Research

Abstract: NUT carcinoma (NC) is a type of aggressive cancer driven by chromosome translocations. Fusion genes between a DNA-binding protein, such as bromodomain and extraterminal domain (BET) proteins, and the testis-specific protein NUTM1 generated by these translocations drive the formation of NC. NC can develop in very young children without significant accumulation of somatic mutations, presenting a relatively clean model to study the genetic etiology of oncogenesis. However, after 20 years of research, a few challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Although the oncogenic impact of the ZNF532:: NUTM1 fusion in CNS tumors has not been studied, functional studies of other cancers have shown that NUTM1 fusion positive cells demonstrate lack of differentiation of epithelial cells and nuclear localization of the NUT protein, suggesting that NUTM1 fusions contribute to tumor development by associating with nuclear chromatin and interfering with cell differentiation [34,35]. Consistent with this finding, nearly all of our patient's tumor cells displayed homogeneous nuclear expression when using the monoclonal NUT antibody, confirming nuclear localization of the NUT protein in this tumor (NeoGenomics; Figure 1K).…”
Section: Discussionmentioning
confidence: 99%
“…Although the oncogenic impact of the ZNF532:: NUTM1 fusion in CNS tumors has not been studied, functional studies of other cancers have shown that NUTM1 fusion positive cells demonstrate lack of differentiation of epithelial cells and nuclear localization of the NUT protein, suggesting that NUTM1 fusions contribute to tumor development by associating with nuclear chromatin and interfering with cell differentiation [34,35]. Consistent with this finding, nearly all of our patient's tumor cells displayed homogeneous nuclear expression when using the monoclonal NUT antibody, confirming nuclear localization of the NUT protein in this tumor (NeoGenomics; Figure 1K).…”
Section: Discussionmentioning
confidence: 99%
“…Although the oncogenic impact of the ZNF532-NUTM1 fusion in CNS tumors has not been studied, functional studies of other cancers have shown that NUTMI- fusion positive cells demonstrate lack of differentiation of epithelial cells and nuclear localization of the NUT protein, suggesting that NUTM1- fusions contributed to tumor development by associating with nuclear chromatin and interfering with cell differentiation [22,23]. Consistent with this finding, nearly all of our patient’s tumor cells displayed homogenous nuclear expression of the monoclonal NUT antibody confirming nuclear localization of the NUT protein in this tumor (NeoGenomics; Figure 1I).…”
Section: Discussionmentioning
confidence: 99%
“…Although the oncogenic impact of the ZNF532-NUTM1 fusion in CNS tumors has not been studied, functional studies of other cancers have shown that NUTMI-fusion positive cells demonstrate lack of differentiation of epithelial cells and nuclear localization of the NUT protein, suggesting that NUTM1fusions contributed to tumor development by associating with nuclear chromatin and interfering with cell differentiation 31,32 . Consistent with this nding, nearly all of our patient's tumor cells displayed homogenous nuclear expression of the monoclonal NUT antibody con rming nuclear localization of the NUT protein in this tumor (NeoGenomics; Fig.…”
Section: Discussionmentioning
confidence: 99%